Efecto De La Ley De Reforma Tributaria 2277 De 2022 En Las Regalías del Petróleo Crudo (2023)
The Tax Reform Law 2277 of 2022 "By Means Of Which A Tax Reform For Equality And Social Justice Is Adopted And Other Provisions Are Dictated" (Congreso de Colombia, 2022, 13 de diciembre) issued by the government of Gustavo Petro Urrego, who is the popularly elected president of Colombia for the period 2022-2026, where the deduction of the expense for royalties in the Income Tax is prohibited, based on this premise, a collection of information was made in different platforms of the State and national legislation, to contextualize what the deduction was of royalties and what will be from now on, having as scope only the royalties of crude oil in Colombia, identifying the most outstanding effects of this and analyzing each possible effect that can directly or indirectly affect the entire country.